Biomechanical effects of high acceleration on the temporomandibular joint. Issue 3 (17th February 2022) - Luo, Haotian; Shu, Jingheng; Liu, Zhan
Abstract: The symptoms of temporomandibular disorders (TMD) are easily developed in pilots after long flights, such as joint pain, anterior displacement disc and so on. Related studies have suggested that abnormal high acceleration would cause temporomandibular joint (TMJ) lesions. Therefore, the purpose of this study is to analyze the biomechanical effects of high acceleration on the TMJs. The 3D models of the maxilla, mandible, articular disc were generated by Computed Tomography (CT) and Magnetic Resonance Imaging (MRI) of a healthy volunteer without any TMD symptoms. Then, the loads were added according to the various operating conditions of the aircraft. The maximum tensile stress, occurred in the anterior band of the discs, exceeded the failure stress. Compared with the low acceleration, the contact stresses between the discs and the articular cartilages were much greater under the high acceleration. High acceleration had a negative impact on the stress distributions of the articular discs and cartilages and easily led to TMJ damage. Lateral acceleration will cause asymmetric stress distribution of the TMJs.